Geometry-Driven Control of Magnetic States and Spin-Wave Modes in Bridged Magnetic Dots - Saavedra-Díaz, E (IOP Publishing Ltd, 2025)
Through micromagnetic simulations, we have investigated the influence of bridge geometry-specifically the modulation parameter lambda-on the static and dynamic magnetic properties of bridged dot nanostructures. Our analysis revealed two distinct magnetic evolution paths: one leading to metastable vortex and antivortex configurations, and another converging to quasi-uniform ferromagnetic states. The dynamic susceptibility spectra show that each magnetic path supports a characteristic set of spin-wave resonance modes, with frequencies and spatial profiles that vary systematically with lambda. We demonstrate that by tuning this geometric parameter, it is possible to achieve precise control over the number, frequency, and spatial localization of spin-wave modes. These findings provide a foundation for designing reconfigurable magnonic devices and open new avenues for the development of geometry-engineered spintronic and signal-processing applications.